(Ba, Ca)(Ti, Zr)O3–CeO2 translucent and opaque ceramics — Optical and electromechanical characteristics. Issue 2 (February 2023) - Bijalwan, Vijay; Kaštyl, Jaroslav; Prajzler, Vladimír; Erhart, Jiří; Pouchlý, Václav; Maca, Karel
Abstract: This work demonstrates promising approaches to synthesize multifunctional-translucent BCZT-CeO2 ceramic for electro-mechanical/optical conversion. Nearly fully dense BCZT-CeO2 electroceramics were fabricated by spark plasma sintering (SPS) showing high dielectric permittivity of 5875 and low dielectric loss of 2.1%. Altogether, an extraordinary optical transmittance was attained as ∼ 40% at 750 nm wavelength and ∼ 46% in the infrared region. The fine grains restricted piezoelectric constant, d33, to a moderate value of ∼ 145 pC/N but with an enhanced Curie temperature, TC ∼ 135 °C. Post rapid pressure-less sintering on SPSed samples led to a fast grain growth within an extra hour of sintering and a major improvement of piezoelectric properties (d33 = 532 pC/N and kp = 43%) was achieved. A substantial amount of energy can be saved by both approaches owing to rapid heating/cooling rates and short dwell-times, at least when compared to conventional sintering. This success highlights ingenious avenues for further studies on BCZT-CeO2 electro-optical ceramics.